Visual Antropology in Latin America Dossier’s Introduction - Andrade, X (2012)
Introduction to the Dossier Part of the process of democratic construction in post-dictatorial Chile is exercising memory. The process of exercising memory is a political, social and subjective labor that legitimizes narratives, makes them visible, and also questions the human rights violations that were perpetrated by the state between 1973 and 1990. This article addresses the role of visual anthropology in the construction of memories and the articulation of testimonies concerning torture case survivors, arguing that audiovisual interviews are a space for dialogue and communicative interaction in which witnesses –through their faces, gestures and emotions– embody testimonial images.